2017
DOI: 10.1016/j.yhbeh.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Potential contribution of progesterone receptors to the development of sexual behavior in male and female mice

Abstract: We previously showed that estradiol can have both defeminizing and feminizing effects on the developing mouse brain. Pre-and early postnatal estradiol defeminized the ability to show lordosis in adulthood, whereas prepubertal estradiol feminized this ability. Furthermore, we found that estradiol upregulates progesterone receptors (PR) during development, inducing both a male-and female-typical pattern of PR expression in the mouse hypothalamus. In the present study, we took advantage of a newly developed PR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Interestingly, neonatal male mice treated with the ZK137316 PR antagonist during the critical period of brain masculinization (P0–P10) display minor abnormalities related to male sexual behavior in adulthood. This is in contrast with the prepubertal treated females (P15–P25) that present an impaired lordosis behavior in adulthood (Desroziers et al, 2017), suggesting that the effects of PR activation (Figure 2) on sexual differentiation are time-dependent and sex-regulated during development.…”
Section: Progesterone Actions During Cns Developmentmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, neonatal male mice treated with the ZK137316 PR antagonist during the critical period of brain masculinization (P0–P10) display minor abnormalities related to male sexual behavior in adulthood. This is in contrast with the prepubertal treated females (P15–P25) that present an impaired lordosis behavior in adulthood (Desroziers et al, 2017), suggesting that the effects of PR activation (Figure 2) on sexual differentiation are time-dependent and sex-regulated during development.…”
Section: Progesterone Actions During Cns Developmentmentioning
confidence: 78%
“…The observed differences in PR expression indicate the existence of a period during neurodevelopment (Figure 3) in which the male brain is more sensitive than that of females to the progesterone actions, more specifically in the structures related to reproductive functions and sexual behavior in adulthood. Interestingly, the increase in the brain PR expression coincides with the period of masculinization induced by androgens during prenatal development in mice (Desroziers et al, 2017). Furthermore, PR expression in the preoptic area and the hypothalamus of developing male rats increases at E18, simultaneously to the beginning of testosterone secretion by testes.…”
Section: Progesterone Actions During Cns Developmentmentioning
confidence: 99%
“…Sexual maturation is affected by cranial irradiation as it can accelerate or inhibit puberty in a dose-dependent manner ( Roth et al, 2000 ), and female mice have likely not acquired a regular estrous cycle ( Goldman et al, 2007 ), a factor that proved to be tightly linked to odor recognition memory in adulthood. Hormone-induced postnatal development of female sexual behaviors occurs later in female mice in comparison to male-typical behaviors ( Brock et al, 2011 ), and in females, specific reproductive behaviors are further influenced by progesterone ( Dey et al, 2015 ) and its receptors ( Desroziers et al, 2017 ), though the role that progesterone plays in the sexually maturing brain remains unclear. In the present study, females showed odor recognition memory only during the metestrus and diestrus estrous stages in adulthood, a period characterized by increasing progesterone ( Wood et al, 2007 ; Aritonang et al, 2017 ), but the same was not found during early adolescence, a period of continuing sexual development.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual partner preference testing was carried out as described by Dresroziers et al . and Angoa‐Perez et al .…”
Section: Methodsmentioning
confidence: 99%